Through the looking glass: self-reassuring meta-cognitive capacity and its relationship with the thematic content of voices - Connor, Charlotte; Birchwood, Max (Frontiers in Human Neuroscience, 2013)
Abstract Aims To examine the self-critical thoughts and self-reassuring meta-cognitive capacity of those who hear voices and explore whether they are associated with the theme of voice content and appraisals of voice power and voice expressed emotion. Method A cross-sectional design was used, combining semi-structured interviews and self-report measures. Data on symptomatology, self-critical thoughts and self-reassuring meta-cognitive capacity, thematic voice content and appraisals of voice power and expressed emotion were collected from 74 voice-hearers in Birmingham, UK. Results Common themes of voice content reflected issues of shame, control and affiliation. Controlling content was the most prevalent theme, however, no significant predictor of this theme was found; shaming thematic voice content linked with reduced capacity to self-reassure following self-critical thoughts. Voice-hearers with the greatest level of self-critical thoughts appraised their voices as powerful and high in voice expressed emotion Conclusions Findings suggest that voice-hearers self-critical thoughts are reflected in the type of relationship they have with their voice. However, access to self-reassuring meta-cognitive capacity may serve as a protective factor for those who hear voices, resulting in more benign voice content. These findings highlight the importance of this specific meta-cognitive capacity and will inform future therapeutic interventions for the management of voices in this vulnerable group.